An Investigation of the Reporting of Questionable Acts in an International Setting - Schultz, Joseph J.; Johnson, Douglas A.; Morris, Deigan; Dyrnes, Sverre (Journal of Accounting Research, 1993)
Joseph J. Schultz, Jr., Douglas A. Johnson, Deigan Morris, Sverre Dyrnes, An Investigation of the Reporting of Questionable Acts in an International Setting, Journal of Accounting Research, Vol. 31, Studies on International Accounting (1993), pp. 75-103